State-of-the-art and perspectives in transition metal-based heterogeneous catalysis for selective hydrogenation of cinnamaldehyde. Issue 1 (February 2023) - Patil, Komal N.; Manikanta, P.; Srinivasappa, Puneethkumar M.; Jadhav, Arvind H.; Nagaraja, Bhari Mallanna
Abstract: Chemoselective liquid phase hydrogenation of cinnamaldehyde (CAL) by employing transition-metal-based heterogeneous catalysts has been investigated by a lot of researchers worldwide with a view to obtain the desired products such as cinnamyl alcohol or hydrocinnamaldehyde. Both the products have significant wide-ranging applications in pharmaceuticals, perfumery, cosmetics and chemical industries. The present review therefore summarizes development in the last five years towards selective CAL hydrogenation over transition metal-based catalysts. The review is categorized into two major sections; selective hydrogenation of CAL to cinnamyl alcohol (COL) and selective hydrogenation of CAL to hydrocinnamaldehyde (HCAL) over various noble metals (Pt, Pd, Ru, Au, Ir and Ag) and non-noble metal-based catalysts (Ni, Co and Cu). A number of tailored metal-based catalytic systems for selective CAL hydrogenation reported in current years have been systematically reviewed based on the above categories. In addition, effect of reaction variables such as catalyst preparation, nature of solvents, reaction conditions has been deliberated. The review has been concluded with discussion on limitations encountered for noble metal as well as non-noble metal-based catalysts for selective CAL hydrogenation along with the future scope. Overall, the present review focuses on the fundamental principles of the transition metal-based catalysts reported for selective CAL hydrogenation. Graphical Abstract: ga1 Highlights: Comprehensive review on transition metal-based catalyst for cinnamaldehyde hydrogenation. Cinnamyl alcohol and hydrocinnamaldehyde products were taken into consideration. Effect of reaction variables on catalytic activity has been deliberated. Features such as modification of electronic and geometric properties of active metal is discussed. The review also discuss limitations encountered for selective CAL hydrogenation.